Bio-Efficacy of Compost Extracts for the Control of Choanephora Wet Rot Okra (Abelmoschus Esculentus L.) - Siddiqui, Yasmeen (2005)
Bio-efficacy of aqueous extracts prepared from rice straw (RST) and empty fruit bunch of oil palm (EFB) composts for the control of Choanephora wet rot of okra (Abelmoschus esculentus L.) was studied. The physiochemical and microbiological properties of both the finished composts showed that they were within the range of compost standards. RST compost extracts has higher N, PI K content of 1.14, 3.36, and 1.42 % with respect to EFB extract with 1.01. 2.51, and 1.20 %, respectively. The aqueous extracts produced therefore are suitable as foliar sprays for the improvement of growth of okra plants. Twelve days of brewing was the best extraction time based on the properties of the compost extracts obtained and their ability to inhibit the growth of C. cucurbitarum in vitro. The percent germination was reduced by 80 to 83 % in the presence of RST and EFB extracts. The effect was further demonstrated by using filter (0.2 pm) and heat - sterilized extracts (autoclaving at 121'~ for 20 minutes) for assessing their potential effect on mycelial growth, conidial germination of C. cucurbitarum and production of inducible resistance related compounds in pre - treated plants. Non - sterilized extracts from both composts gave significantly reduced (P 10.05) mycelial growth of C. cucurbitarum (84 and 79 % for RST and EFB extracts, respectively) and enhanced host resistance through production of inducible compounds such as total phenols, peroxidase (PO), polyphenol oxidase (PPO) and phenylalanine ammonia lyase (PAL) in okra plants. The eficacy was perceptibly reduced by filter sterilizing the RST and EFB extracts to 57 and 55 %, respectively, whereas heat sterilization nullifies their activity totally, suggesting that the activity of both extracts were biological in nature. The higher activity of filter-sterilized extracts associated with mycelial growth inhibition and percentage disease reduction as compared to heat - sterilized extracts infers that chemical factors and nutrient composition of the extracts also played a role in the activity. Humic acids (active component of humic substances in compost) extracted from RST and EFB compost extracts when tested in vitro reduced mycelial growth of C. cucurbitarum by 100 and 64.2 % at 1 % concentration, respectively. The bio-efficacy was further enhanced by fortifying the extracts with T. harzianum, an established biocontrol agent against many pathogens. Trichoderma - fortified extracts (3 x l ~ - ~ cmf ul-') from RST when tested on okra in glass house and field conditions showed significant increase in plant growth and yield. There was reduction of 91.9 % in Choanephora wet rot of okra at 12 weeks of assessment in field and was comparable to Dithane M- 4503 and significantly higher to T. harzianum fortified EFB extracts.